Weaver Ants Provide Ecosystem Services to Tropical Tree Crops - Thurman, Jessa H.; Northfield, Tobin D.; Snyder, William E. (Frontiers in Ecology and Evolution, 2019)
Generalist predators bring a complex mix of beneficial and harmful effects to agroecosystems. When these predators feed on herbivorous pests, biological control is improved with the potential to increase crop yield. However, generalists often feed on predators, pollinators, and plants, which might worsen pest outbreaks and reduce fruit set. For example, weaver ants (Oecophylla smaragdina) are major predators of several key, economically-damaging pest insects of tropical fruit and nut crops. Yet the ants also attack other predatory arthropods and important pollinators, while tending trophobiont honeydew producers like mealybugs (Pseudococcidae) that are themselves pests. Finally, ants will supplement their diet with sugars from floral and extrafloral nectaries, a form of plant feeding that presumably carries a physiological cost to the plant. Here, across previously-published experimental studies that compared treatments where ants were present versus excluded, we summarize the effects of weaver ants on beneficial and pest insects and tree-crop productivity. Our quantitative review revealed nearly ubiquitous benefits of Oecophylla ants for tropical agriculture. Treatments with ants present generally showed lower pest densities and damage from pest insects in the families Coreidae, Miridae, Pentatomidae, and Tephritidae. Pest reduction was seen on cacao (Theobroma cacao), cashew (Anacardium occidentale), and mango (Mangifera indica) trees. The exception to these pest reductions occurred when ants facilitated the population growth of mealybugs and other honeydew producers, which are rarely considered pests. In general, we found that Oecophylla ants provided the valuable ecosystem service of natural pest control to a diversity of tropical tree crops. Despite the potential for the ants to harm other predators or pollinators, evidence for these ecosystem disservices was rare and other beneficial insects co-exist well with this group of ants. Our findings bolster the general finding that ant species that tend herbivores who are not themselves pests can provide broad-reaching benefits to plant productivity. More generally, our findings are consistent with the many cases where non-pest prey bolster densities of polyphagous predators with benefits for biological control despite some degree of plant feeding by the predators.